The public papers of Governor Simeon Willis, 1943-1947 - Willis, Simeon S., 1879-1965 (Public papers of the governors of Kentucky., 1988)
During the period from 1931 to 1967 -- thirty-six years -- Kentuckians elected only one Republican as governor of the Commonwealth. Yet that man, a former justice of the state's highest court, seldom appears as other than a footnote in the standard histories. That is unfortunate, for Simeon Willis of Ashland made a fine record as governor, assuming the office during World War II and leaving it strengthened in a postwar world. In this new volume in the Public Papers of the Governors of Kentucky series, editor James C. Klotter has assembled 173 documents and public statements, so that the Willis.